Anticancer Activity and Cisplatin Binding Ability of Bis-Quinoline and Bis-Isoquinoline Derived [Pd2L4]4+ Metallosupramolecular Cages - Vasdev, Roan A. S.; Gaudin, Lachlan F.; Preston, Dan; Jogy, Jackmil P.; Giles, Gregory I.; Crowley, James D. (Frontiers in Chemistry, 2018)
New bis-quinoline (Lq) and bis-isoquinoline-based (Liq) ligands have been synthesised, along with their respective homoleptic [Pd2(Lq or Liq)4]4+ cages (Cq and Ciq). The ligands and cages were characterised by 1H, 13C and diffusion ordered (DOSY) NMR spectroscopies, high resolution electrospray ionization mass spectrometry (HR-ESIMS) and in the case of the bis-quinoline cage, X-ray crystallography. The crystal structure of Cq architecture showed that the [Pd2(Lq)4]4+ cage formed a twisted meso isomer where the [Pd(quinoline)4]4+ units at either end of the cage architecture adopt the opposite twists (left and right handed). Conversely, Density Functional Theory (DFT) calculations on the Ciq cage architecture indicated that a lantern shaped conformation similar to what has been observed before for related [Pd2(Ltripy)4]4+ systems (where Ltripy = 2,6-bis(pyridin-3-ylethynyl)pyridine) was generated. The different cage conformations manifest different properties for the isomeric cages. The Ciq cage is able to bind, weakly in acetonitrile, the anticancer drug cisplatin whereas the Cq architecture shows no interaction with the guest under the same conditions. The kinetic robustness of the two cages in the presence of Cl- nucleophiles was also different. The Ciq cage was completely decomposed into free Liq and [Pd(Cl)4]2- within two hours. However, the Cq cage was more long lived and was only fully decomposed after seven hours. The new ligands (Liq and Lq) and the Pd(II) cage architectures (Ciq and Cq) were assessed for their cytotoxic properties against two cancerous cell lines (A549 lung cancer and MDA-MB231 breast cancer) and one non-cancerous cell line (HDFa skin cells). It was found that Lq and Cq were both reasonably cytotoxic (IC50 = 0.5 μM and 0.5 μM, respectively) against A549, while Ciq was slightly less active (IC50 = 7.4 μM). Liq was not soluble enough to allow the IC50 to be determined against either of the two cancerous cell lines. However, none of the molecules showed any selectively for the cancer cells, they were all found to have similar cytotoxicity against HDFa skin cells (IC50 values ranged from 2.6 – 3.0 μM).